Vertebral refracture after percutaneous vertebroplasty for osteoporotic vertebral compression fractures with and without brace wearing: A retrospective study of 300 patients - Xinyu, Guo; Na, Zhu; Haihong, Zhang; Dingjun, Hao (Frontiers in Surgery, 2023)
Background: To study the clinical incidence rate of vertebral body fracture after percutaneous vertebroplasty (PVP) with and without brace wearing and provide a new guiding ideology for preventing vertebral fracture after surgery in the clinic. Results: All patients were followed up from 8-24 months (mean 22.4 months). Compared with preoperation, the age, sex, BMI, bone density, ODI, VAS, and Cobb angle between refracture and no refracture were not statistically significant. The VAS, ODI, and JOA scores were significantly improved in the brace-wearing group compared with the no bracing group(P < 0 05). The incidence of vertebral refracture in the brace-wearing group was lower than that in the non-brace-wearing group, and there was a significant difference between the two groups (P < 0.05). Three months after operation，the JOA score in the soft brace group was significantly higher than that in the rigid brace group (P < 0 05). During the last follow-up, it was found that the VAS score, the incidence of refracture and ODI, there was not a difference between the soft brace group and the rigid brace group(P >0.05). The improvement in the JOA score in the soft brace group was better than that in the rigid brace group, and there was a significant difference between the groups (P < 0 05). Conclusion: To sum up, brace improved the prognosis in terms of quality of life and postoperative subjective perception. The presence of a brace can relieve postoperative residual pain. In contrast, wearing a soft brace can give patients a better medical experience.